The whirlwind of war : voices of the storm, 1861-1865 - Oates, Stephen B. (New York : HarperCollins, 1998)
The Whirlwind of War is the second book in prize-winning historian and biographer Stephen B. Oates' extraordinary Voices of the Storm trilogy, which began with The Approaching Fury, Oates' compelling narrative about the 40 tumultuous years that led to "America's Armageddon.
The Winds of 'Sixty-One -- The Winds of 'Sixty-Two -- The Winds of 'Sixty-Three -- The Winds of 'Sixty-Four -- The Winds of 'Sixty-Five -- Coda.
Includes bibliographical references (p. [715]-807) and index.
Keywords: United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Biography